Penerapan Video Animasi IPA Berbasis Saintifik Untuk Meningkatkan Hasil Belajar Siswa Kelas VIII - Sakinah, Fera Nur; Amin, Ahmad; Gumay, Ovilia Putri Utami (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2025)
This research aims to determine the improvement in learning outcomes of class VIII students at SMP YP Bakti Ibu 11 Lubuklinggau after implementing scientific-based science animation videos. The researcher also conducted interviews with class VIII students at SMP YP Bakti Ibu 11 Lubuklinggau who thought that physics science lessons had a lot of formulas and a lot of calculated material, therefore the view emerged from class VIII students at SMP YP Bakti Ibu 11 Lubuklinggau that physics science lessons were difficult. In learning process conditions like this, the learning process is mostly monotonous and the learning atmosphere is passive. Even though the learning media at school are in the form of textbooks, power points and e-modules, students should be more creative in looking for learning media from various sources. So with the background of the problem based on interviews with teachers and students, we need a physical science learning media that attracts students' attention and makes students motivated in learning Physics Science which is considered difficult because there are many calculations, and can support the learning process in the 2013 curriculum, so the researcher wants to implement scientific-based science animation video learning media which aims to make it easier for teachers to convey learning material concisely, and attract students' attention so that they are motivated to learn physics science so that students no longer think that physics science lessons are difficult because of the large number of calculations and formulas.